Studies on Some Bacterial Toxins and Clinical Characteristics of Children in Benghazi Children’s Hospital, Libya - Elsharia, Hanan Saad; Masoud, Reem A. (The 1st International Conference On Basic Sciences & Its Applictionss, 2024)
This research aims to identify the types of bacteria ,Know the types of toxins they secrete and heath problems they cause,know the seasons of the year in which they are most infectecd,and know the types of antibiotics that are most sensitive and resistant to them,and over time they become unresponsitive to medications after that, which leads to the spread of diseases and difficulty of treating them.And increased mortality rate .Bacteria produce many toxins that differ depending on their type. Escherichia coli ,which secretes Shiga toxins, causes hemorrhagic colitis,and also secretes intestinal toxins that cause diarrhhea in children.Staphylococcus aures secretes many toxins that decompose red or white blood cells and secretes α-toxin(α-hemolysin Or Hla) This study concluded that the bacteria Pseudomonas and the highest number of infections was 120, aged from one month to a year. These types of infections caused acute and chronic infections, skin rashes, and other infections .The least of them were infected with Staphylococcus epidermidis, and they numbered 25 from the age of 6 to 10 years. Also, the season of the year in which infections occur the most is the winter season, as the number of infections was the highest with 274.Whereas the least season for infection is spring with only 1Sensitivity and resistance of bacteria to antibiotics, as Staphylococcusepidermidis, was the most resistant to the antibiotic Ciprofloxacin and numbered 72, Staphylococcus albus was the least sensitive to Carbapenems and numbered 9, Pseudomonas was the most sensitive to Impenem and numbered 147, and E.coli was the least sensitive species to antibiotics .